JUNK FOOD DALAM SUMBER IDE PENCIPTAAN SENI GRAFIS - DIMAS CANDRA KHARISMAWAN; DYAH YUNI KURNIAWATI (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2022)
This final project expresses the writer's imagination in the form of graphic art, which is inspired by the dangers of junk food today in Indonesia. The problem is discussed by approach; 1. What is meant by junk food ?, 2. Why was junk food chosen as the theme of graphic art creation ?, 3. What is the form of visualizing junk food in graphic works using linoleum cuttings techniques? In its implementation, the phenomenon of the current danger of junk food in Indonesia is creatively reprocessed according to the taste of the author, works are printed using air-based color ink on cardboard paper, 10 printed works are each printed in 3 editions inspired by the situation. now. Each work is framed by using adjustable size frames. It is hoped that this work can be used as inspiration and provide knowledge about the current dangers of junk food in Indonesia. It is hoped that this work can be enjoyed by all who see it as well as art observers and art lovers.